Clinical diagnosis progress and continuing medical education - N A Mukhin; A A Svistunov; V V Fomin (Терапевтический архив, 2014)
The paper discusses current approaches to diagnosing in an internal medicine clinic and to improving diagnostic tactics. It gives prospects for training physicians in current diagnostic approaches in the framework of the continuing medical education system.